2020
DOI: 10.1088/1402-4896/aba5ad
|View full text |Cite
|
Sign up to set email alerts
|

Effects of combined material and geometric nonlinearities on dynamic response of embedded nanobeams

Abstract: Exact prediction of the mechanical behavior of nano-sensors and nano-actuators directly depends on the models applied to analyze their nano-components. From their dynamic behavior point of view, despite many studies related to the geometrical nonlinearities in modeling the nanostructures, one of the main issues that has not been addressed appropriately is the effects of material nonlinearity. Hence, this paper intends to fill this gap and deals with an investigation of combined geometrical and material nonline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Since researchers have adopted this theory, numerous investigations have widely confirmed its effectiveness in computing the induced behavioral shift due to the effect of small sizes for components with nanometric dimensions [33]. Presently, analyses have applied the nonlocal approach to various types of materials [34,35] to determine both linear [36] and nonlinear [33] vibrations for uniform or nonuniform [37,38] cross-sections. Ghorbanpour Arani et al [39] concluded that the shift in local behavior with respect to nonlocal behavior increases according to a parametric function in relation to the wave number.…”
Section: Introductionmentioning
confidence: 99%
“…Since researchers have adopted this theory, numerous investigations have widely confirmed its effectiveness in computing the induced behavioral shift due to the effect of small sizes for components with nanometric dimensions [33]. Presently, analyses have applied the nonlocal approach to various types of materials [34,35] to determine both linear [36] and nonlinear [33] vibrations for uniform or nonuniform [37,38] cross-sections. Ghorbanpour Arani et al [39] concluded that the shift in local behavior with respect to nonlocal behavior increases according to a parametric function in relation to the wave number.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, modifications in classical continuum theory have been made to incorporate small-scale/nonlocal effects. As a result of this, various nonlocal continuum theories such as couple stress theory (CST) [8], strain gradient theory (SGT) [9], Eringen's nonlocal theory (ENT) [10][11][12][13], nonlocal strain gradient theory (NSGT) [14,15] and surface elasticity theory [16,17] have been proposed. Using these theories, a vast literature dealing with the mechanical behavior of FG nanostructures is available, and Ghayesh and Farajpour [18] have presented a critical review of work up to 2019 [18].…”
Section: Introductionmentioning
confidence: 99%
“…Remarkable features of CNTs, however, cannot be precisely realized applying the classical approach of the elasticity theory. A great attention is, accordingly, devoted in the recent literature to the generalized elasticity theories, such as nonlocal elasticity approach [6][7][8][9][10][11][12][13][14][15][16], strain gradient theory [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31], and unified elasticity frameworks [32][33][34][35][36][37][38][39][40][41][42][43][44], for nanoscopic study of the field quantities.…”
Section: Introductionmentioning
confidence: 99%